2019
DOI: 10.1002/jctb.6153
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5‐hydroxymethylfurfural from fructose and inulin catalyzed by magnetically‐recoverable Fe3O4@SiO2@TiO2–HPW nanoparticles

Abstract: BACKGROUND 5‐Hydroxymethylfurfural (HMF) is an important platform chemical that can be generated from biomass using catalysts and used for the production of biofuels and biobased polymers. RESULTS In this study, a novel magnetically‐recoverable catalyst (Fe3O4@SiO2@TiO2−HPW) was synthesized for the first time by immobilizing H3PW12O40 (HPW) on the surfaces of SiO2 and TiO2‐coated Fe3O4 nanoparticles. A number of techniques, including inductively coupled plasma (ICP) spectroscopy, transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
(173 reference statements)
0
9
0
Order By: Relevance
“…5C is related to the Ti-O-Ti bond. This is clear evidence that the TiO 2 layer was correctly formed on Fe 3 O 4 @SiO 2 [39]. The peaks at 1272 and 1491 cm -1 (Fig.…”
Section: Characterization Of the Samplesmentioning
confidence: 55%
“…5C is related to the Ti-O-Ti bond. This is clear evidence that the TiO 2 layer was correctly formed on Fe 3 O 4 @SiO 2 [39]. The peaks at 1272 and 1491 cm -1 (Fig.…”
Section: Characterization Of the Samplesmentioning
confidence: 55%
“…A broad absorption peak between 400 cm −1 and 800 cm −1 in figure 5(C) was related to the Ti-O-Ti bond. This is clear evidence that TiO 2 layer was correctly formed on the Fe 3 O 4 /SiO 2 [28]. The peaks at 1196 cm −1 , 1568 cm −1 and 964 cm −1 (figures 5(D)-(F)) related with the C-N, C=C and C-H bond revealed that FST/PPy was correctly prepared [29].…”
Section: Characterization Of Samplesmentioning
confidence: 62%
“…As the temperature and reaction time increased, the glucose conversion increased and almost wholly converted at a higher reaction temperature or a longer reaction time 13 . However, after reaching a specific optimum reaction temperature and prolonging the reaction time, the yield of HMF will gradually decrease, which led to HMF rehydration and polymerization to generate undesired byproducts 15,28,37,38 …”
Section: Factor That Affecting the Production Rate Of 5‐hmfmentioning
confidence: 99%
“…These catalysts include strong mineral‐acids catalysts, zeolites, metal oxides and minerals, functionalized silica materials, and heteropolyacids 21,34 . However, over the decades, homogeneous catalysts exhibit several shortcomings include the difficulties and high cost for complete‐separation and recovery process of catalysts from the product, increased risk for equipment corrosion, the generation of environmental pollution risk and these homogeneous catalysts have limited application which not suitable for broad industrial/commercial‐scale application 25,35‐42 . The simple summaries of previous studies for the catalytic conversion of HMF are summarized in Table 1 for readers to find the details readily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation